Communication Patterns of The Indonesian Ulema Council's Fatwa on Friday Prayers Virtually - Aulia Laila Safitri; Fitri Fadlilah; Indy Fathina Izza; Ahmada Ghina Ghoniah; Alyah Dwi Soraya; Naila Zakiyatun Nafsiyah; Naura Zahrania (International Tatho Academics, 2025)
The covid 19 pandemic that hit Indonesia caused several impacts on Indonesian society that had not happened before. one them, the phenomenon of Juma'at prayers that are carried out virtually. This study aims to examine the pattern of mass communication in harmonizing the MUI (Indonesian Ulema Council) fatwa on virtual Friday prayers, its effectiveness in building public understanding, and its influence on the implementation of the fatwa during the pandemic. Qualitative studies in the form of literature studies that collect and analyze literature sources. The results show that MUI (Indonesian Ulema Council) fatwa has three broad communication functions, namely helping to maintain religious values and norms in society, as legal guidelines and social tools that influence people's behavior, and showing unique changes in devotional practices in the digital era. MUI (Indonesian Ulema Council) fatwas show an important role in disseminating religious guidance and maintaining social cohesion in the midst of change. This study strengthens the theory of mass communication as an instrument of social influence in religious contexts by focusing solely on communication patterns and community responses to fatwas.